The Association Between Psychotropic Drug Use and Fertility Problems Among Male Subjects - Solomon, Ronnie; Shvartsur, Rachel; Azab, Abed N (Journal of psychiatric practice, 2019)
Mental disorders affect a high percentage of the general population and are associated with a significant burden. One major component of treatment for mental illnesses is pharmacotherapy. Various psychotropic medications are used in the treatment of psychiatric disorders and these are often associated with a plethora of side effects. The many side effects of psychotropic drugs can severely impair patients' quality of life and decrease their adherence to treatment. Among the relatively neglected and less-studied potential side effects of psychotropic drugs are impairment of sperm parameters and fertility problems among male patients. This article summarizes the data with regard to the effects of 6 widely used psychotropic drugs-lithium, valproate, haloperidol, olanzapine, imipramine, and fluoxetine-on sexual function and sperm parameters in male subjects. In general, the reviewed data suggest that these medications can be associated with sexual function problems and negative effects on sperm parameters among male subjects. It is important to note that most of the data are based on preclinical studies and nonrandomized clinical trials with relatively small sample sizes, so that it is not possible to draw unequivocal conclusions with regard to the clinical relevance of the findings. Prospective, randomized clinical trials are necessary to elucidate the effects of psychotropic drugs on men's sperm parameters and fertility indices per se.